Proyecto integral de acondicionamiento físico de un centro poblado menor: Faccha, Matahuasi, Concepción, Región Andrés Avelino Cáceres - Sánchez Carrera, Dante Pedro (Universidad Nacional Federico Villarreal, 1990)
Proyecto integral de acondicionamiento físico de un centro poblado menor: Faccha, Matahuasi, Concepción, Región Andrés Avelino Cáceres.
Keywords: Proyecto; Integral; Acondicionamiento; Físico; Centro; Poblado; Menor; Faccha; Matahuasi; Concepción; Región; Andrés; Avelino; Cáceres; https://purl.org/pe-repo/ocde/ford#2.07.01